A Comparison Study of Tangible and Intangible Culture as Commercialisation Process of Tourism Village in Yogyakarta - Rudwiarti, Lucia Asdra; Pudianti, Anna; Vitasurya, Vincentia Reni (E-Journal of Tourism; Volume 4 Number 2 (September 2017), 2017)
The paper is an empirical study examining the tangible and intangible culture of rural tourism with a focus on rural transformation from daily local into commercial behaviour due to presence of tourism activities. It explores the process of commercialization of tangible and intangible culture. The case studies of Brayut and Pentingsari rural tourism village are studied through observation and interviews of physical and non-physical transformation with community members and the rural tourism manager. Both villages are the unique growing tourist village in Yogyakarta, but Brayut has a potential asset of maintained condition  traditional Javanese house in whereas Pentingsari has an attractive natural of green village with the local cultural heritage. The qualitative empirical research study was applied to explore the transformation of cultural meaning by the locals before and after commercialization process. Firstly, the study reviewed the original tangible and intangible culture before transformation. Secondly, changes in cultural functions and meaning are analyzed in the current situation caused by its transforming into commercial activities. By examining the comparison of tangible and intangible culture in the commercializing process is built to understand the relationships between the two and the quality of its transformation.